Antipyics bilateral paradental cysts: clinicopathological correlation in two cases - Momesso, Nataira Regina; Costa, Beethoven Estevão; Senko, Ricardo Alexandre G; Matsumoto, Mariza Akemi; Silva, Andréia Aparecida da; Ribeiro-Junior, Paulo Domingos (Journal of Oral Diagnosis, 2020)
A paradental cyst (PC) is an odontogenic lesion, which occurs near the cervical margin of the lateral surface of the root because of an inflammatory process. Generally, they are located on the buccal and distal faces of completely or partially erupted third molar teeth. The purpose of this article is to discuss two uncommon clinical cases of a bilateral PC associated with third molars. Its diagnosed from clinical and radiographic examinations. The diagnosis of a PC was established following the correlation of radiographic, surgical, and microscopic features.